Influence of Friction Stir Welding Rotation Speeds In dwell phase on the Temperature Distribution of AA6061-T6 Aluminum Alloy Weldment - Abed, Rasheed Nema (Al-Nahrain Journal for Engineering Sciences, 2017)
Friction Stir welding (FSW) parameters, which play a vital principle, that impact on the mechanical, microstructural properties of the weldment because of the warmth produced by the contact between the instrument and work-piece, An AA6061-T6 aluminum composite plate with measurements (186*150*4) mm3 welded through various rotational paces 800, 1000, 1200 and 1450 rpm, the created heat measured through thermocouples embedded in study zones of the Weldment, a Finite Element model have been executed by utilizing ANSYS 12.1 bundle charges to ponder the temperature appropriation amid stay stage, the outcomes demonstrates a decent assention between the after effects of exploratory and hypothetical tests. The most extreme temperature measured at this condition was 0.71 from the liquefying temperature of the sample at a maximum rotational speed of (1450) r/min.